2005
DOI: 10.1037/0096-3445.134.3.291
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Locus Coeruleus in Mediating the Attentional Blink: A Neurocomputational Theory.

Abstract: The attentional blink refers to the transient impairment in perceiving the 2nd of 2 targets presented in close temporal proximity. In this article, the authors propose a neurobiological mechanism for this effect. The authors extend a recently developed computational model of the potentiating influence of the locus coeruleus-norepinephrine system on information processing and hypothesize that a refractoriness in the function of this system may account for the attentional blink. The model accurately simulates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
229
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(252 citation statements)
references
References 84 publications
20
229
3
Order By: Relevance
“…Both are initiated by detection of a salient stimulus and their temporal characteristics are similar. Nieuwenhuis et al's (2005) model is also consistent with a temporal, rather than sequential (by-item), interpretation of blink onset. That is, it suggests that the blink has a fixed temporal dynamic, the onset of which is not regulated by intervening distractors, as explored in Prediction 1 (see Section 5.1).…”
Section: Assessment and Comparison To Stsupporting
confidence: 70%
See 1 more Smart Citation
“…Both are initiated by detection of a salient stimulus and their temporal characteristics are similar. Nieuwenhuis et al's (2005) model is also consistent with a temporal, rather than sequential (by-item), interpretation of blink onset. That is, it suggests that the blink has a fixed temporal dynamic, the onset of which is not regulated by intervening distractors, as explored in Prediction 1 (see Section 5.1).…”
Section: Assessment and Comparison To Stsupporting
confidence: 70%
“…In addition, the effect of LC innervation includes amplification of excitatory responses for feature selective cells, and in a visual discrimination paradigm, monkey LC neurons were activated with a temporal profile that seems to match the AB. This observation prompted Nieuwenhuis et al's (2005) model; see Figure 25. The model can be divided into two components: the behavior network (comprising the input, decision, and detection layers) and the LC.…”
Section: The Lc Modelmentioning
confidence: 97%
“…As proposed by Wyble, Bowman, and Potter (2007), the sparing of a second target at SOAs of less than 100 ms may reflect the time course of a transient attentional response launched upon detection of the first target (for a related proposal see Nieuwenhuis, Gilzenrat, Holmes & Cohen, 2005). The hypothesized effect is similar to the transient attention produced by a spatial cue to the location of an upcoming target (Nakayama & Mackeben, 1989).…”
Section: Discussionmentioning
confidence: 85%
“…In support of this claim, Wyble et al showed that detecting a categorically defined target amongst distractors elicits a spatio-temporal window of enhanced processing that shares many of the characteristics of the transient attentional response described by Nakayama and Mackeben. Further support for a role of transient attention in sparing can be found in studies that show that sparing still occurs for the second of two targets separated by a distractor, as long as these targets appear at an SOA of less than about 100 ms (Bowman & Wyble, 2007; see also Potter et al, 2002, andNieuwenhuis et al, 2005).…”
Section: Discussionmentioning
confidence: 90%
“…6 of Seiffert & DiLollo, 1997) may be reinterpreted as actually reflecting enhanced (or increased probability of) selection of the post-T1 distractor, resulting in stronger suppression of subsequent items. Interestingly, Nieuwenhuis, Gilzenrat, Holmes, and Cohen (2005) have recently proposed that the attentional blink is related to the phasic response of the locus coeruleus (LC), a nucleus in the brain stem largely responsible for the noradrenergic innervation of the cortex. The LC is highly sensitive to the behavioral relevance of stimuli, and its activity may well reflect or cause the initial enhancement and subsequent suppression of the input.…”
Section: An Alternative Account: the Overinvestment Hypothesismentioning
confidence: 99%